Mesenchymal stromal cells as prophylaxis for graft-versus-host disease in haplo-identical hematopoietic stem cell transplantation recipients with severe aplastic anemia?—a systematic review and meta-analysis - Ruonan Li; Jingke Tu; Jingyu Zhao; Hong Pan; Liwei Fang; Jun Shi (Stem Cell Research & Therapy, 2021)
Abstract Background Mesenchymal stromal cells (MSCs) are an emerging prophylaxis option for graft-versus-host disease (GVHD) in haplo-identical hematopoietic stem cell transplantation (haplo-HSCT) recipients with severe aplastic anemia (SAA), but studies have reported inconsistent results. This systematic review and meta-analysis evaluates the efficacy of MSCs as prophylaxis for GVHD in SAA patients with haplo-HSCT. Methods Studies were retrieved from PubMed, EMBASE, Cochrane, Web of Science, and http://clinicaltrials.gov from establishment to February 2020. Twenty-nine single-arm studies (n = 1456) were included, in which eight (n = 241) studies combined with MSCs and eleven (n = 1215) reports without MSCs in haplo-HSCT for SAA patients. The primary outcomes were the incidences of GVHD. Other outcomes included 2-year overall survival (OS) and the incidence of cytomegalovirus (CMV) infection. Odds ratios (ORs) were calculated to compare the results pooled through random or fixed effects models. Results Between MSCs and no MSCs groups, no significant differences were found in the pooled incidences of acute GVHD (56.0%, 95% CI 48.6–63.5% vs. 47.2%, 95% CI 29.0–65.4%; OR 1.43, 95% CI 0.91–2.25; p = 0.123), grade II–IV acute GVHD (29.8%, 95% CI 24.1–35.5% vs. 30.6%, 95% CI 26.6–34.6%; OR 0.97, 95% CI 0.70–1.32; p = 0.889), and chronic GVHD (25.4%, 95% CI 19.8–31.0% vs. 30.0%, 95% CI 23.3–36.6%; OR 0.79, 95% CI 0.56–1.11; p = 0.187). Furtherly, there was no obvious difference in 2-year OS (OR 0.98, 95% CI 0.60–1.61; p = 1.000) and incidence of CMV infection (OR 0.61, 95% CI 0.40–1.92; p = 0.018). Conclusions Our meta-analysis indicates that the prophylactic use of MSC co-transplantation is not an effective option for SAA patients undergoing haplo-HSCT. Hence, the general co-transplantation of MSCs for SAA haplo-HSCT recipients may lack evidence-based practice.